Well-being pedagogy in English language teaching: A systematic literature review - Ika Meilinda Ummul Ma’rufa; Joko Widodo; Nurul Zuriah; Arisandi Setiyawan (Universitas Islam Negeri Palangka Raya, Indonesia, 2026)
Well-being pedagogy has attracted the attention of researchers in various disciplines. Although well-being pedagogy has been widely discussed in education, a clearer understanding of how it is integrated into English language teaching (ELT) is still needed. This systematic literature review seeks to explore current trends, key thematic areas, and notable gaps in the literature, intending to offer insights into strategies for effectively incorporating well-being into ELT. This research uses Scopus as the main data source for the initial data search through the database to the selection of studies for synthesis according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The findings reveal several important trends. First, research on well-being in ELT has gradually increased over time, with a noticeable rise after 2020. Second, most studies are located within the social sciences, indicating that well-being is mainly examined from educational and social perspectives. Third, a large proportion of publications originates from developed countries. The research indicates that existing studies mainly focus on supportive learning environments, teacher support, and the integration of innovative pedagogical approaches to enhance learning experiences. The study implies that it should provide practical approaches for integrating well-being pedagogy into ELT classrooms.